2014
DOI: 10.3201/eid2009.140115
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe Influenza A–Related Pneumonia in Adult Cohort, Mexico, 2013–14

Abstract: During the 2013–14 influenza season, we assessed characteristics of 102 adults with suspected influenza pneumonia in a hospital in Mexico; most were unvaccinated. More comorbidities and severity of illness were found than for patients admitted during the 2009–10 influenza pandemic. Vaccination policies should focus on risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
2
6
1
Order By: Relevance
“…Pregnancy was present in one patient and she was underwent C/S in the ICU. obesity which has bMI > 30, pregnancy, and diabetes mellitus were the most frequently seen comorbid conditions (2,(10)(11)(12). Contrary to the literature, obesity was not seen as a risk factor in this study.…”
Section: Discussioncontrasting
confidence: 77%
“…Pregnancy was present in one patient and she was underwent C/S in the ICU. obesity which has bMI > 30, pregnancy, and diabetes mellitus were the most frequently seen comorbid conditions (2,(10)(11)(12). Contrary to the literature, obesity was not seen as a risk factor in this study.…”
Section: Discussioncontrasting
confidence: 77%
“…Young children and the elderly contribute most to mortality in seasonal flu, while pandemic scenarios are notable for their tendency to generate greater mortality or serious complications among groups that do not normally experience strong illness, such as adults under 65 [5, 18, 47, 48, 42]. These events are characterized by different distributions of age risk: an initial pandemic wave may be dominated by morbidity among school-aged children, and some empirical and modeling studies suggest that adults are more likely to become infected in the season following a pandemic [9, 10, 11, 12, 13]. While the mechanisms for this remain poor understood, it has been suggested that there is an accumulation of heterologous immunity with age [49].…”
Section: Discussionmentioning
confidence: 99%
“…Influenza virus genetic and antigenic data suggests that severity is linked to hemagglutinin protein novelty [3], and A/H3-dominant seasons have greater mortality rates than A/H1 or B dominant seasons [4, 5, 6, 7] as H3 strains disproportionately affect older populations [8]. Epidemiological studies of seasons following pandemics suggest that novel antigenic strains shift the expected age-related immune landscape, which generates relatively high susceptibility among adults [9, 10, 11, 12, 5, 13]. In congruence with a link between severity and low pre-existing immunity, high T cell concentrations correlate with subsiding illness and high viral shedding correlates with high clinical severity[14].…”
Section: Introductionmentioning
confidence: 99%
“…It was not within the scope of our study to conduct an analysis of risk factors for A/H1N1 death. However, findings from a recent study based on epidemiological data for 102 adults with suspected influenza pneumonia and admitted to a hospital in Mexico indicate that unvaccinated status against A/H1N1 influenza and presence of comorbidities were frequently reported among the study cohort (30). …”
Section: Discussionmentioning
confidence: 99%